Application of Virgin Coconut Oil (VCO) Massage and Repositioning in Decubitus Ulcers of Patients with Multiple Complications: A Case Study - Yasmine, Hanna Alya; Rahayu, Urip; Pahria, Tuti (Universitas Padjadjaran, 2026)
Patients with peritoneal abscesses who are immobilized are at risk of decubitus ulcer. Various complications in patients such as malnutrition and anaemia in patients cause a decrease in body immunity, causing a high risk of decubitus ulcers and difficulty in wound healing. Massage using Virgin Coconut Oil (VCO) and repositioning are combined interventions to reduce the risk and healing of decubitus ulcers. The study aims to determine the results of massage using VCO and repositioning patients with decubitus ulcers in healing and efforts to prevent decubitus ulcer effectively. The study is a case report of the application of massage using VCO and repositioning in a patient with decubitus ulcer with intraperitoneal abscess, pneumonia, malnutrition, and anaemia at Sumedang Regional Hospital. The patient is a 33-year-old woman with grade 2 decubitus ulcers in the sacrum area which appeared red, serum, skin peeling, and shallow holes. The patient was selected for treatment due to the decubitus ulcers, high risk of decubitus ulcers, and the absence of any interventions. Massage with VCO and repositioning were performed twice daily for 6 days. The interventions were carried out consistently by researchers, nurses, patients, and their families. There were a decrease in degree 2 to degree 1 in the patient’s sacrum decubitus ulcers after massage using VCO and repositioning.